PENCEMARAN KUALITAS OLI ENGINE EXCAVATOR ALAT BERAT KELAS SEBELAS TON AKIBAT KEAUSAN KOMPONEN - Nofriyandi R Nofriyandi (Jurnal Ilmiah Poli Rekayasa, 2022)
In this study, the focus is on the analysis of oil quality pollution caused by the thirst of the components in the engine. [7]Komponen bagian dalam engine yang dialiri oleh pelumas sangat berpotensi terjadinya kehausan yang diakibatkan oleh pergesekkan antara material yang beroperasi dalam sistem kerja engine. Oil in the engine has specifications or properties that will affect engine performance. In this study, the authors took samples on the diesel engine oil multi grade S.A.E 15W-40 which was applied to an excavator heavy equipment engine with a capacity of eleven tons. One type of Additives in engine oil is Anti-Wear which functions to reduce wear by coating the surface with an oil film. The focus of this research will be to see how much thirst occurs in the internal components of the engine that are flowing with oil. The thirst of components in the engine will be seen from the quality of the engine oil, if the thirst that occurs is greater then the work of anti-wear additives in the oil has begun to decrease so there must be a solution or analysis obtained. Test results on tests from the S.O.S. laboratory From the six sampling times, the highest wear metal value was 35 ppm at the time of operation of the 1665 Meter [Hr] unit. Based on the results of the test, it is stated that the excavator engine is in good condition when viewed from the wear metal, oil contaminant, oil condition and oil viscosity.